A comparative observational study based on two radiographic techniques in suspected unilateral mandibular condylar fracture - Shereen Fatima; Mohammad Ali R Patel; Aaisha Siddiqa; Neelakamal Hallur; Mohammed Arshad Hussain; Mohammed Haneef (Wolters Kluwer Medknow Publications, 2020)
Objective: This hypothetical comparative study aimed to compare two radiographic techniques based on the traditional radiograph (orthopantomography [OPG]) and computed tomography (CT) scans and find the best radiographic techniques to be used to confirm diagnostic accuracy and treatment planning in suspected unilateral condylar fractures. Materials and Methods: All patients with suspected unilateral condylar fractures were initially subjected to a radiologic assessment through a conventional radiographic technique of OPG to select the treatment modality, that is, open or closed. Subsequently, all patients were made to undergo a standard CT scan for the study of the temporomandibular joint, with the same objective, that is, (eighty radiographic imaging: forty OPG + forty CT scan) was done to determine which radiographic technique is more helpful in determining the final clinical diagnosis including treatment planning of suspected unilateral mandible condyle fracture. The findings were compared and cross-checked with those of conventional radiographic analysis. Results: It was found that out of the selected patients of confirmed forty unilateral condylar fractures, 33 patients were indicated for closed reduction by conventional radiography, were revealed to have a lateral extracapsular displacement on CT scan, and hence were treated by open reduction. Seven patients satisfied the criteria for closed reduction, both by conventional radiographs and CT scans. Conclusion: Through this theoretical research, it was found that both radiographic techniques are indispensable, specific, and standard in the detection of mandibular fractures. It was noted that CT scan radiographic information might help alter the approach and the treatment plan and prevent erroneous management in mandibular condylar fractures.